2014
DOI: 10.2522/ptj.20130175
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Sedentary Behaviors in People With Stroke Living in the Community: A Systematic Review

Abstract: Little is known about the time people with stroke spend being sedentary each day or the pattern in which sedentary time is accumulated. Studies using objective, reliable, and valid measures of sedentary time are needed to further investigate the effects of sedentary time on the health of people with stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
172
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(181 citation statements)
references
References 51 publications
5
172
1
3
Order By: Relevance
“…The results of this study have shown that ambulatory subacute stroke patients have a significantly lower PA level than that of a population of It is well known that a sustained decline in PA is common among stroke patients in the chronic term (29). It is also known that the PA levels of stroke patients are low in acute stroke wards (12,30).…”
Section: Discussionmentioning
confidence: 70%
“…The results of this study have shown that ambulatory subacute stroke patients have a significantly lower PA level than that of a population of It is well known that a sustained decline in PA is common among stroke patients in the chronic term (29). It is also known that the PA levels of stroke patients are low in acute stroke wards (12,30).…”
Section: Discussionmentioning
confidence: 70%
“…It is possible that prolonged sitting and sedentary behaviours start early after stroke survivors return home. In future, investigation of activity behaviours after stroke should also include measurement of sedentary behaviours such as sitting 2,27 and physical activity interventions should also target reducing daily sitting time to reduce risk of chronic disease in this group 28 .…”
Section: Discussionmentioning
confidence: 99%
“…However, by the chronic phase of recovery, stroke survivors commonly adopt sedentary activity behaviours 2 . For example, after stroke, daily step counts are reported to range from 1400 3 to 6195 4 steps/day, indicating that the overall volume of activity after stroke is mostly below that required for general health benefits (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This shift in thinking creates measurement challenges, since sedentary behaviour in people with stroke has been traditionally measured in a number of ways, both subjectively and objectively. Subjectively, sedentary behaviour has most frequently been measured by self-report using activity questionnaires [14]. Objectively, accelerometers have become the standard method of measurement to collect information regarding the intensity of movement [15].…”
Section: Sedentary Behaviour In People With Stroke?mentioning
confidence: 99%